Gelingensbedingungen für den Aufbau einer forschenden Grundhaltung – eine qualitative vergleichende Fallstudie - Homt, Martina; van Ophuysen, Stefanie

Forschend Lernen in Praxissemester und Lehrerberuf – die Einstellung von Lehramtsstudierenden - Homt, Martina; van Ophuysen, Stefanie

Gelingensbedingungen für die Implementation Forschenden Lernens – eine qualitative vergleichende Fallstudie - Homt, Martina; van Ophuysen, Stefanie

Wie lernt man „forschendes Lernen“? Die Konzeption der Methodenausbildung für Lehramtsstudierende an der WWU Münster und erste Evaluationsergebnisse - Behrmann, Lars; Homt, Martina; Schmidt, Jennifer; van Ophuysen, Stefanie

Zwei Testformate: vergleichbare Ergebnisse? Mathematikabiturklausuren und standardisierte Testaufgaben - Weischenberg, Julia; Eickelmann, Birgit (Zeitschrift für Schulentwicklung und Schulmanagement Baden-Württemberg)

Informationskompetenz als Aufgabe von Schule - Eickelmann, Birgit (Handbuch Informationskompetenz)

Mobiles Lernen und computer- und informationsbezogene Kompetenzen von Achtklässlerinnen und Achtklässlern - Schaumburg, Heike; Prasse, Doreen; Eickelmann, Birgit; Gerick, Julia (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

Perspektiven von Schulleitungen auf neue Technologien in Schule und Unterricht - Gerick, Julia; Eickelmann, Birgit; Drossel, Kerstin; Lorenz, Ramona (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

Der Erwerb von computer- und informationsbezogenen Kompetenzen von Ganztags- und Halbtagsschülerinnen und -schülern im Vergleich - Eickelmann, Birgit; Rollett, Wolfram; Weischenberg, Julia; Vennemann, Mario (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen

Eine Bilanz zur Integration digitaler Medien an Grundschulen in Deutschland aus international vergleichender Perspektive - Eickelmann, Birgit (Neue Medien in der Grundschule 2.0. Grundlagen - Konzepte - Perspektiven)

High-stakes testing and Educational Governance – Insights and innovations in European school systems. Special Issue Editorial - Lorenz, Ramona; Eickelmann, Birgit; Bos, Wilfried (Journal for Educational Research Online (JERO))

Schulische Innovationen im Kontext digitaler Bildung – eine Betrachtung aus der Lehrerperspektive - Gerick, Julia; Eickelmann, Birgit (Zeitschrift Schul-Management)

Digital natives or just kids with smartphones? - The story of ICILS in Germany - Eickelmann, Birgit (IEA Newsletter)

Zur Relevanz informatischer Bildung in der Schule für den Erwerb computer- und informationsbezogener Kompetenzen als Teil von Medienbildung – Ergebnisse für Deutschland und die Schweiz im internationalen Vergleich - Eickelmann, Birgit; Drossel, Kerstin (Zeitschrift MedienPädagogik)

Schule digital – der Länderindikator 2016. Kompetenzen von Lehrpersonen der Sekundarstufe I im Umgang mit digitalen Medien im Bundesländervergleich

Kooperation von Lehrkräften der Sekundarstufe I zum Einsatz digitaler Medien in Lehr- und Lernprozessen in Deutschland und im Bundesländervergleich - Welling, Stefan; Lorenz, Ramona; Eickelmann, Birgit (Schule digital – der Länderindikator 2016. Kompetenzen von Lehrpersonen der Sekundarstufe I im Umgang mit digitalen Medien im Bundesländervergleich)

Die eingeschätzte Relevanz der Phasen der Lehrerausbildung hinsichtlich der Vermittlung didaktischer und methodischer Kompetenzen von Lehrpersonen für den schulischen Einsatz digitaler Medien in Deutschland und im Bundesländervergleich - Eickelmann, Birgit; Lorenz, Ramona; Endberg, Manuela (Schule digital – der Länderindikator 2016. Kompetenzen von Lehrpersonen der Sekundarstufe I im Umgang mit digitalen Medien im Bundesländervergleich)

Additive Fertigungsverfahren im Kontext von Industrie 4.0 - Klemp, Eric; Pottebaum, Jens (Handbuch Industrie 4.0 Bd.3)

Fatigue crack growth behavior and mechanical properties of additively processed EN AW-7075 aluminium alloy - Reschetnik, Wadim; Brüggemann, Jan-Peter; Aydinöz, Mehmet Esat; Grydin, Olexandr; Hoyer, Kay-Peter; Kullmer, Gunter; Richard, Hans Albert (Procedia Structural Integrity)

Stochastic recursive inclusion in two timescales with an application to the lagrangian dual problem - Ramaswamy, Arunselvan; Bhatnagar, Shalabh (Stochastics)

Dokumentenorientierte NoSQL-Datenbanken in skalierbaren Webanwendungen - Eine Analyse am Beispiel von MongoDB und der Webanwendung PINGO - Bach, Christoph; Kundisch, Dennis; Neumann, Jürgen; Schlangenotto, Darius; Whittaker, Michael (HMD Praxis der Wirtschaftsinformatik)

Grundsatzfragen der Abwärmenutzung. Effizienzsteigerungspotenziale in der Industrie durch Abwärmenutzung erschließen. - Philipp, Matthias; Schumm, Gregor; Schlosser, Florian; Hechelmann, Ron-Hendrik; Holzhammer, Uwe (BWK Energie-Fachmagazin)

Hybrid-heating-systems for optimized integration of low-temperature-heat and renewable energy - Schumm, Gregor; Philipp, Matthias; Schlosser, Florian; Hesselbach, Jens; Walmsley, Timothy G.; Atkins, Martin J. (Chemical Engineering Transactions)

Hardware in the Loop Evaluation of a Hybrid Heating System for Increased Energy Efficiency and Management - Schumm, Gregor; Philipp, Matthias; Schlosser, Florian; Hesselbach, Jens; Walmsley, Timothy G.; Atkins, Martin J.

Stackelberg Competition among Intermediaries in a Differentiated Duopoly with Product Innovation - Manegold, Jochen
On an intermediate goods market we consider vertical and horizontal product differentiation and analyze the impact of simultaneous competition for resources and the demand of customers on the market outcome. Asymmetries between intermediaries may arise due to distinct product qualities as well as by reasons of different production technologies. The intermediaries compete on the output market by choosing production quantities sequentially and for the supplies of a monopolistic input supplier on the input market. It turns out that there exist differences in product quality and productivities such that an intermediary being the Stackelberg leader has no incentive to procure inputs, whereas in the role of the Stackelberg follower will participate in the market. Moreover, we find that given an intermediary is more competitive, his equilibrium output quantity is higher when being the leader than when being the follower. Interestingly, if the intermediary is less competitive and goods are complements, there may exist asymmetries such that an intermediary being in the position of the Stackelberg follower offers higher output quantities in equilibrium than when being in the position of the Stackelberg leader.
Keywords: Input Market; Product Quality; Quantity Competition; Stackelberg Competition; Product Innovation

Modelling of temperatures and heat flow within laser sintered part cakes - Josupeit, Stefan; Ordia, Lavish; Schmid, Hans-Joachim (Additive Manufacturing)
Temperature effects in the polymer laser sintering process are an important aspect regarding the process reproducibility and part quality. Depending on the job layout and position within the part cake, individual temperature histories occur during the process. Temperature history dependent effects are for example part warpage, the crystallization rate and powder ageing effects. This work focuses on temperatures and heat flow within laser sintered part cakes. Therefore, a thermal Finite Element (FE) model of a part cake is developed based on experimental in-process temperature measurements. Thermal boundary conditions and properties of the used bulk polymer powder are analyzed and relevant parameters are identified. The model is validated and optimized considering different job heights and ambient conditions during the cooling phase. It is finally possible to predict position-dependent temperature histories as a function of significant job parameters. The model allows a transfer of the results for varied boundary conditions during cooling. In combination with an implementation of built parts, this model will be an important tool for the development of optimized process controls and cooling strategies.

Guard ring induced distortion of the steady velocity profile in a parallel plate rheometer - Schmid, Hans-Joachim; Pieper, S. (Applied Rheology)
The shape and fracture of the free surface frequently limits the measuring range and impedes the use of optical velocimetric techniques in parallel plate and cone plate setups. To prevent this, various kinds of edge guards are often employed. In the present study, we elucidate how an edge guard distorts the steady velocity profile in a parallel plate setup. To this end, we analyzed the velocity field of a strongly shear-thinning fluid, a Newtonian fluid and a set of suspensions via particle image velocimetry in a parallel plate device. Several guard ring sizes were studied. The distortion is described by a simple three parameter model. These parameters are mostly constant for different fluids and suspensions with particle volume fractions below 45%. With increasing radius, the guard ring.s influence approaches a limiting value that we attribute to the influence of the fluid surrounding the gap. Our results indicate a limiting ratio of the difference between plate radius and guard to gap size that should always be exceeded. In the presence of a guard ring, even Newtonian fluids do not exhibit a constant shear rate for most radial distances within the gap. This distortion of the velocity field challenges the simple superposition approach of unguarded device and guard influence that is prevalent in the literature.

Layer-formation of non-colloidal suspensions in a parallel plate rheometer under steady shear - Pieper, Sven; Schmid, Hans-Joachim (Journal of Non-Newtonian Fluid Mechanics)
Suspensions are subject to confinement induced structuring, i.e. layering, at the confining surfaces. While most of the previous work focused on layering in Couette cells, the present study aimed to characterize the resulting layers at the plates of a parallel plate rheometer with regard to their relative particle concentration. The particle concentration profile over the radial distance was characterized for various mean concentrations and gap heights. To this end, we mapped the distribution of fluorescently dyed tracer particles in density and refractive index matched suspensions. The results indicate that layering at the surfaces stabilizes as the ratio between gap height and particle diameter increases. For lower gap heights, i.e. as the suspension approaches a two dimensional state, the layer concentration was non-uniform over the plates. In general, results were quantitatively different for the upper and lower plate and the concentration profiles were noticeably asymmetric. We conclude that this is probably the result of the rheometer loading or the start-up process. The stable layers as well as the inhomogeneous particle distribution in general offer an explanation for the lack of transferability of viscosimetric results between different setups.

Auswahl internationaler Standorte - Wie lassen sich Standortentscheidungen methodisch unterstützen? - Betz, Stefan (ForschungsForum Paderborn)

Experimental perfect state transfer of an entangled photonic qubit - Chapman, Robert J.; Santandrea, Matteo; Huang, Zixin; Corrielli, Giacomo; Crespi, Andrea; Yung, Man-Hong; Osellame, Roberto; Peruzzo, Alberto (Nature Communications)

Systematik zur innovationsorientierten Kompetenzplanung - Rübbelke, René

Systematik zur technologie-induzierten Produkt- und Technologieplanung - Wall, Marina

Selfish Network Creation - On Variants of Network Creation Games - Cord-Landwehr, Andreas

Instrumentarium für einen lösungsmusterbasierten Entwurf fortgeschrittener mechatronischer Systeme - Anacker, Harald

Methodik zur Bewertung von Produktionssystemen in der frühen Entwicklungsphase - Rudtsch, Vinzent

Systematik zur lösungsmusterbasierten Entwicklung von Frugal Innovations - Lehner, Anne-Christin

Systematik zur musterbasierten Entwicklung technologie-induzierter Geschäftsmodelle - Amshoff, Benjamin

Multipartite Entanglement of a Two-Separable State - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Quantum Correlations from the Conditional Statistics of Incomplete Data - Sperling, Jan; Bartley, Tim; Donati, G.; Barbieri, M.; Jin, X.-M.; Datta, A.; Vogel, W.; Walmsley, I. A. (Physical Review Letters)

Gaussian entanglement in the turbulent atmosphere - Bohmann, M.; Semenov, A. A.; Sperling, Jan; Vogel, W. (Physical Review A)

Operational definition of quantum correlations of light - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review A)

Characterizing maximally singular phase-space distributions - Sperling, Jan (Physical Review A)

Multitime correlation functions in nonclassical stochastic processes - Krumm, F.; Sperling, Jan; Vogel, W. (Physical Review A)

Witnessing random unitary and projective quantum channels: Complementarity between separable and maximally entangled states - Bruns, D.; Sperling, Jan; Scheel, S. (Physical Review A)

Harnessing click detectors for the genuine characterization of light states - Heilmann, René; Sperling, Jan; Perez-Leija, Armando; Gräfe, Markus; Heinrich, Matthias; Nolte, Stefan; Vogel, Werner; Szameit, Alexander (Scientific Reports)

Health Shocks and Risk Aversion - Schmitz, Hendrik; Decker, S. (Journal of Health Economics 50, 154-170)

Design of virtual research environments for {\ "u} r detailed philological work - Keil, Reinhard ("Eh, the old man, I would like to pay attention". Festschrift for {\ "u} r Joachim Veit for his 60th birthday)

Decentralized provenance-aware publishing with nanopublications - Kuhn, Tobias; Chichester, Christine; Krauthammer, Michael; Queralt-Rosinach, Núria; Verborgh, Ruben; Giannakopoulos, George; Ngonga Ngomo, Axel-Cyrille; Viglianti, Raffaele; Dumontier, Michel (PeerJ Comput. Sci.)

A fine-grained evaluation of SPARQL endpoint federation systems - Saleem, Muhammad; Khan, Yasar; Hasnain, Ali; Ermilov, Ivan; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

An Efficient Approach for the Generation of Allen Relations - Georgala, Kleanthi; Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (ECAI 2016 - 22nd European Conference on Artificial Intelligence, 29 August-2 September 2016, The Hague, The Netherlands - Including Prestigious Applications of Artificial Intelligence {(PAIS} 2016))

Towards SPARQL-Based Induction for Large-Scale RDF Data Sets - Bin, Simon; Bühmann, Lorenz; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (ECAI 2016 - 22nd European Conference on Artificial Intelligence, 29 August-2 September 2016, The Hague, The Netherlands - Including Prestigious Applications of Artificial Intelligence {(PAIS} 2016))

TAIPAN: Automatic Property Mapping for Tabular Data - Ermilov, Ivan; Ngonga Ngomo, Axel-Cyrille (Knowledge Engineering and Knowledge Management - 20th International Conference, EKAW 2016, Bologna, Italy, November 19-23, 2016, Proceedings)

DBtrends: Publishing and Benchmarking RDF Ranking Functions - Marx, Edgard; Zaveri, Amrapali; Mohammed, Mofeed; Rautenberg, Sandro; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille; Cheng, Gong (Proceedings of the 2nd International Workshop on Summarizing and Presenting Entities and Ontologies (SumPre 2016) co-located with the 13th Extended Semantic Web Conference {(ESWC} 2016), Anissaras, Greece, May 30, 2016)

6th Open Challenge on Question Answering over Linked Data (QALD-6) - Unger, Christina; Ngonga Ngomo, Axel-Cyrille; Cabrio, Elena (Semantic Web Challenges - Third SemWebEval Challenge at ESWC 2016, Heraklion, Crete, Greece, May 29 - June 2, 2016, Revised Selected Papers)

The Lazy Traveling Salesman - Memory Management for Large-Scale Link Discovery - Ngonga Ngomo, Axel-Cyrille; M. Hassan, Mofeed (The Semantic Web. Latest Advances and New Domains - 13th International Conference, ESWC 2016, Heraklion, Crete, Greece, May 29 - June 2, 2016, Proceedings)

Federated Query Processing: Challenges and Opportunities - Ngonga Ngomo, Axel-Cyrille; Saleem, Muhammad (Proceedings of the 3rd International Workshop on Dataset PROFIling and fEderated Search for Linked Data {(PROFILES} '16) co-located with the 13th ESWC 2016 Conference, Anissaras, Greece, May 30, 2016)

UPSP: Unique Predicate-based Source Selection for SPARQL Endpoint Federation - Cem Ozkan, Ethem; Saleem, Muhammad; Dogdu, Erdogan; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 3rd International Workshop on Dataset PROFIling and fEderated Search for Linked Data {(PROFILES} '16) co-located with the 13th ESWC 2016 Conference, Anissaras, Greece, May 30, 2016)

Detecting Similar Linked Datasets Using Topic Modelling - Röder, Michael; Ngonga Ngomo, Axel-Cyrille; Ermilov, Ivan; Both, Andreas (The Semantic Web. Latest Advances and New Domains - 13th International Conference, ESWC 2016, Heraklion, Crete, Greece, May 29 - June 2, 2016, Proceedings)

Big data architecture for the semantic analysis of complex events in manufacturing - F. Huber, Marco; Voigt, Martin; Ngonga Ngomo, Axel-Cyrille (46. Jahrestagung der Gesellschaft für Informatik, Informatik von Menschen für Menschen, INFORMATIK 2016, Klagenfurt, Austria, September 26-30, 2016)

Requirements to Modern Semantic Search Engine - Usbeck, Ricardo; Röder, Michael; Haase, Peter; Kozlov, Artem; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (Knowledge Engineering and Semantic Web - 7th International Conference, KESW 2016, Prague, Czech Republic, September 21-23, 2016, Proceedings)

Exploring Term Networks for Semantic Search over RDF Knowledge Graphs - Marx, Edgard; Höffner, Konrad; Shekarpour, Saeedeh; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens; Auer, Sören (Metadata and Semantics Research - 10th International Conference, MTSR 2016, Göttingen, Germany, November 22-25, 2016, Proceedings)

Instance matching benchmark for spatial data: a challenge proposal to OAEI - Fundulaki, Irini; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th International Workshop on Ontology Matching co-located with the 15th International Semantic Web Conference {(ISWC} 2016), Kobe, Japan, October 18, 2016)

How Well Does Your Instance Matching System Perform? Experimental Evaluation with LANCE - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Workshop on Benchmarking Linked Data {(BLINK} 2016) co-located with the 15th International Semantic Web Conference (ISWC), Kobe, Japan, October 18, 2016)

Lion's Den: feeding the LinkLion - Ahmed Sherif, Mohamed; M. Hassan, Mofeed; Soru, Tommaso; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (Proceedings of the 11th International Workshop on Ontology Matching co-located with the 15th International Semantic Web Conference {(ISWC} 2016), Kobe, Japan, October 18, 2016)

Big Data Acquisition - Lyko, Klaus; Nitzschke, Marcus; Ngonga Ngomo, Axel-Cyrille (New Horizons for a Data-Driven Economy - A Roadmap for Usage and Exploitation of Big Data in Europe)

Knowledge Engineering and Semantic Web - 7th International Conference, KESW 2016, Prague, Czech Republic, September 21-23, 2016, Proceedings

Proceedings of the Workshop on Benchmarking Linked Data (BLINK 2016) co-located with the 15th International Semantic Web Conference (ISWC), Kobe, Japan, October 18, 2016

LITMUS: An Open Extensible Framework for Benchmarking RDF Data Management Solutions - Thakkar, Harsh; Dubey, Mohnish; Sejdiu, Gezim; Ngonga Ngomo, Axel-Cyrille; Debattista, Jeremy; Lange, Christoph; Lehmann, Jens; Auer, Sören; Vidal, Maria-Esther (CoRR)

Self-Wiring Question Answering Systems - Usbeck, Ricardo; Huthmann, Jonathan; Duldhardt, Nico; Ngonga Ngomo, Axel-Cyrille (CoRR)

Annex: Radon - Rapid Discovery of Topological Relations - Ahmed Sherif, Mohamed; Dreßler, Kevin; Smeros, Panayiotis; Ngonga Ngomo, Axel-Cyrille (CoRR)

An Evaluation of Models for Runtime Approximation in Link Discovery - Georgala, Kleanthi; Hoffmann, Michael; Ngonga Ngomo, Axel-Cyrille (CoRR)

HOBBIT: Holistic Benchmarking of Big Linked Data - Ngonga Ngomo, Axel-Cyrille; García-Rojas, Alejandra; Fundulaki, Irini (ERCIM News)

Decentralized provenance-aware publishing with nanopublications - Kuhn, Tobias; Chichester, Christine; Krauthammer, Michael; Queralt-Rosinach, Núria; Verborgh, Ruben; Giannakopoulos, George; Ngonga Ngomo, Axel-Cyrille; Viglianti, Raffaele; Dumontier, Michel (PeerJ Prepr.)

Driven discrete time quantum walks - Hamilton, Craig S; Barkhofen, Sonja; Sansoni, Linda; Jex, Igor; Silberhorn, Christine (New Journal of Physics)

Quantum walks with dynamical control: graph engineering, initial state preparation and state transfer - Nitsche, Thomas; Elster, Fabian; Novotný, Jaroslav; Gábris, Aurél; Jex, Igor; Barkhofen, Sonja; Silberhorn, Christine (New Journal of Physics)

Vorstellungen von Studentinnen und Studenten des Lehramts an Grundschulen in Bezug auf die Gestaltung des individualisierten, inklusiven Unterrichts - Hellmich, Frank; Görel, Gamze; Ort, Margarita (Individualisierung im Grundschulunterricht: Anspruch, Realisierung und Risiken)

Erfahrungen und Selbstwirksamkeitsüberzeugungen in Bezug auf inklusiven Unterricht bei Grundschullehrkräften - Hellmich, Frank; Görel, Gamze (Facetten grundschulpädagogischer und -didaktischer Forschung)

Einstellungen und Motivation von Lehramtsstudentinnen und -studenten in Bezug auf den inklusiven Unterricht in der Grundschule. Ein Vergleich zwischen Deutschland und Österreich - Hellmich, Frank; Görel, Gamze; Schwab, Susanne (Empirische Sonderpädagogik)
In Folge der Ratifizierung der UN-Konvention über die Rechte von Menschen mit Behinderungen durch die deutschsprachigen Länder ergeben sich an verschiedenen Stellen in den Bildungssystemen Herausforderungen, die es zukünftig mit dem Blick auf die Gestaltung inklusiver Bildungsprozesse erfolgreich zu bewältigen gilt. Im Besonderen stellt sich gegenwärtig die Frage nach effizienten Möglichkeiten der Ausbildung angehender Lehrerinnen und Lehrer für inklusive Schulen. In unserer Studie untersuchen wir einerseits Unterschiede in Einstellungen zur Inklusion, Selbstwirksamkeitsüberzeugungen, Motivation sowie Erfahrungen aus dem integrativen bzw. inklusiven Unterricht im Rahmen von Schulpraktika zwischen Lehramtsstudentinnen und -studenten mit dem Studienschwerpunkt Grundschule aus Deutschland (N=765) und Österreich (N=519). Die Ergebnisse geben Hinweise darauf, dass die österreichischen Studentinnen und Studenten über signifikant positivere Einstellungen zur Inklusion sowie über signifikant höhere Selbstwirksamkeitsüberzeugungen in Bezug auf die zukünftige Gestaltung inklusiven Unterrichts verfügen als die deutschen Studentinnen und Studenten. Darüber hinaus wird anhand von Strukturgleichungsmodellen deutlich, dass sich Einstellungen zur Inklusion in beiden Stichproben über die Selbstwirksamkeitsüberzeugungen sowie über die Erfahrungen mit inklusivem Unterricht aus Schulpraktika bei den Studentinnen und Studenten erklären lassen. Die Motivation, sich im Studium mit inklusionspädagogischen Fragestellungen zu beschäftigen, wird in beiden Stichproben über die Einstellungen zur Inklusion vorhergesagt. (DIPF/Orig.)

Kognitiv-mathematische Förderung - Hellmich, Frank (Arbeitsfelder der Kindheitspädagogik. Eine Einführung)

Lehren und Lernen im Geometrieunterricht - Hellmich, Frank (Didaktik des Unterrichts im Förderschwerpunkt Lernen. Ein Handbuch für Studium und Praxis)

Reanalyzing Zero Returns to Education in Germany - Kamhöfer, Daniel A.; Schmitz, Hendrik (Journal of Applied Econometrics)

Lesestrategien und Wortschatzarbeit zur Förderung der Lesekompetenzen von mehrsprachig aufwachsenden Kindern in der Grundschule - Hellmich, Frank; Niebuhr-Siebert, Sandra (Leseförderung mit (mehrsprachigen) Kindern in Grundschulen. Wortschatz, Lesetempo und Leseflüssigkeit fördern)

Gleichstellung und innerfamiliale Arbeitsteilung. Mahlzeitenmuster und Beköstigungsarbeit in Familien im Zeitvergleich - Klünder, Nina; Meier-Gräwe, Uta (Wie die Zeit vergeht. Analysen zur Zeitverwendung in Deutschland. Beiträge zur Ergebniskonferenz der Zeitverwendungserhebung)

Ermüdungsverhalten und mikrostrukturelle Charakterisierung der im Laserschmelzverfahren hergestellten Nickelbasis-Superlegierung Inconel 939 - Kanagarajah, Pirabagini
In der vorliegenden Arbeit wurden die mikrostrukturellen Eigenschaften und das dadurch resultierende mechanische Verhalten der im SLM-Verfahren (Selective Laser Melting) hergestellten Nickelbasis-Superlegierung Inconel 939 untersucht und einer Inconel 939 Gusslegierung gegenübergestellt. Die monotonen und mikrostrukturellen Untersuchungsergebnisse zeigen eine eindeutige Abhängigkeit der Herstellungsrichtung und deutliche Unterschiede zur Gusslegierung, insbesondere in der Mikrostruktur. Dehnungsgeregelte isotherme und thermomechanische Ermüdungsversuche in Kombination mit der Methode der digitalen Bildkorrelation (DIC) beschreiben das mechanische Verhalten sowie die kritischen Bereiche im Gefüge. Ob beim SLM- oder Gusswerkstoff eine höhere Lebensdauer bei der isothermen Ermüdung erreicht wird, ist von der Höhe der Beanspruchung abhängig. Im ausscheidungsgehärteten Zustand besitzt das SLM-Material bei niedrigen Belastungen und Temperaturen von Raumtemperatur bis 750 °C eine höhere Lebensdauer und zeigt somit ein besseres Ermüdungsverhalten als der Gusswerkstoff. Bei höheren Dehnungsamplituden werden vorhandene Poren aktiviert und ein schnelles Versagen tritt ein. Mit geeigneten HIP-Parametern konnte die Porosität allerdings deutlich reduziert werden.
Keywords: Nickelbasis-Superlegierung; Inconel 939; Laserschmelzverfahren; SLM; Ermüdung; Mikrostruktur

Glycaemic and insulin index of four common German breads - Goletzke, J; Atkinson, F S; Ek, K L; Bell, K; Brand-Miller, J C; Buyken, Anette (European Journal of Clinical Nutrition)

Commercial complementary food consumption is prospectively associated with added sugar intake in childhood - Foterek, Kristina; Buyken, Anette; Bolzenius, Katja; Hilbig, Annett; Nöthlings, Ute; Alexy, Ute (British Journal of Nutrition)
Abstract Given that commercial complementary food (CF) can contain high levels of added sugar, a high consumption may predispose to a preference for sweet taste later in life. This study examined cross-sectional associations between commercial CF consumption and added sugar intake in infancy as well as its prospective relation to added sugar intake in pre-school and primary-school age children. In all, 288 children of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study with 3-d weighed dietary records at 0·5 and 0·75 (infancy), 3 and 4 (pre-school age) and 6 and 7 years of age (primary-school age) were included in this analysis. Individual commercial CF consumption as percentage of total commercial CF (%cCF) was averaged at 0·5 and 0·75 years. Individual total added sugar intake (g/d, energy percentage/d) was averaged for all three age groups. Multivariable logistic and linear regression models were used to analyse associations between %cCF and added sugar intake. In infancy, a higher %cCF was associated with odds for high added sugar intake from CF and for high total added sugar intake (>75th percentile, P <0·033). Prospectively, a higher %cCF was related to higher added sugar intake in both pre-school ( P <0·041) and primary-school age children ( P <0·039), although these associations were attenuated in models adjusting for added sugar intake in infancy. A higher %cCF in infancy may predispose to higher added sugar intake in later childhood by virtue of its added sugar content. Therefore, offering home-made CF or carefully chosen commercial CF without added sugar might be one strategy to reduce sugar intake in infancy and later on.

Age and time trends in eating frequency and duration of nightly fasting of German children and adolescents - Roßbach, Sarah; Diederichs, Tanja; Bolzenius, Katja; Herder, Christian; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)

Prospective associations of meat consumption during childhood with measures of body composition during adolescence: results from the GINIplus and LISAplus birth cohorts. - Harris, C; Buyken, Anette; von Berg, A; Berdel, D; Lehmann, I; Hoffmann, B; Koletzko, S; Koletzko, B; Heinrich, J; Standl, M (Nutr J)

Residential Energy Storage from Repurposed Electric Vehicle Batteries — Market Overview and Development of a Service-Centered Business Model - Bräuer, sebastian; Monhof, Markus; Klör, Benjamin; Beverungen, Daniel (Proceedings of the IEEE Conference on Business Informatics (CBI 2016))

Modeling and simulation of metallic, particle-damped spheres for lightweight materials - Steinle, Tobias
Lightweight materials play an ever growing role in today's world. Saving on the mass of a machine will usually translate into a lower energy consumption. However, lightweight applications are prone to develop performance problems due to vibration induced by the operation of the machine. The Fraunhofer Institute for Manufacturing Technology and Advanced Materials in Dresden conducts research into the damping properties of composite materials. They are experimenting with hollow, particle filled spheres embedded in the lightweight material. Such a system is the technical motivation of this thesis. Ultimately, a numerical experiment to derive the coefficient of restitution is required. The simulation developed in this thesis is based on a discrete element method to track the individual particle and sphere trajectories. Based on a potential based approach for the particle interactions deployed in molecular dynamics, the behavior of the particles can be controlled effectively. The simulated volume is using reflecting boundaries and encloses the hollow sphere. In this work, a highly flexible memory structure was used with a linked cell approach to cope with the highly flexible mass of particles. This allows for a linear complexity of the method in regard to the particle number by reducing the computational overhead of the interaction computation. Multiple numerical experiments show the great effect the particles have on the damping behavior of the system.

Monitoring in Franchise-Netzwerken: Eine ökonomische Analyse - Breuer, Robin

Informationsasymmetrien auf dem Spendenmarkt und Möglichkeiten ihrer Reduktion: Eine Prinzipal-Agenten-Perspektive von Online Spenden - Amedick, Michaela

Pairwise versus Pointwise Ranking: A Case Study - Melnikov, Vitalik; Hüllermeier, Eyke; Kaimann, Daniel; Frick, Bernd; Gupta, Pritha (Schedae Informaticae)

Multiobjective Optimal Control Methods for the Development of an Intelligent Cruise Control - Dellnitz, Michael; Eckstein, Julian; Flaßkamp, Kathrin; Friedel, Patrick; Horenkamp, Christian; Köhler, Ulrich; Ober-Blöbaum, Sina; Peitz, Sebastian; Tiemeyer, Sebastian (Progress in Industrial Mathematics at ECMI)

Second harmonic generation spectroscopy on hybrid plasmonic/dielectric nanoantennas - Linnenbank, Heiko; Grynko, Yevgen; Förstner, Jens; Linden, Stefan (Light: Science & Applications)
Keywords: tet_topic_opticalantenna; tet_topic_shg

Oblique incidence of semi-guided waves on step-like folds in planar dielectric slabs: Lossless vertical interconnects in 3D integrated photonic circuits - Hildebrandt, Andre; Alhaddad, Samer; Hammer, Manfred; Förstner, Jens (Integrated Optics: Devices, Materials, and Technologies XX)
Keywords: tet_topic_waveguide

Bildungsarbeit in Wirtschaft und Betrieb - Harteis, Christian; Heid, Helmut (Handbuch Bildungsforschung)

A News Editorial Corpus for Mining Argumentation Strategies - Al Khatib, Khalid; Wachsmuth, Henning; Kiesel, Johannes; Hagen, Matthias; Stein, Benno (Proceedings of COLING 2016, the 26th International Conference on Computational Linguistics: Technical Papers)

Silicon oxynitride microdisk resonators for integrated waveguide coupling - Hett, Thomas; Frers, Torsten; Widhalm, Alex; Berth, Gerhard; Hilleringmann, Ulrich; Zrenner, Artur (Smart Systems Integration 2016 - International Conference and Exhibition on Integration Issues of Miniaturized Systems, SSI 2016)